Faith, Equity, and Development - Pinglé, Vibha (Washington, DC: World Bank, 2012)
The rise of identity politics has given resurgence to a variety of religious movements in the last few decades that have seriously challenged the ideas enshrined in the Universal Declaration of Human Rights (UDHR). At least three factors appear to have influenced the extent to and manner in which, these movements have negotiated identity politics and challenged the UDHR. These are: 1) the extent of intra-religious competition in the country; 2) the effectiveness of governance in the country; and 3) whether the focus of the religious movement is on Western or traditional notions of development.